Computational thinking-based informatics material recommendation system for vocational school students with the content-based filtering method - Fitri, Zahratul; Safriana, Safriana; Nurdin, Nurdin (Edelweiss Applied Science and Technology, 2024)
The system is built by displaying the results of material recommendations and the results of the accuracy test of student material recommendation scores based on students' computational thinking. The processes carried out are tokenization, stopword removal, stemming, and weighting. The results of the extraction were then compared using the cosine similarity approach. The greater the cosine-similarity value produced, the more similar the two data are, so that the material recommendations will be based on the smallest cosine-similarity value between the extraction of student recommendation data. The system built has met the needs of functionality that answer the results of the problem analysis determined at the beginning of the research. This is by the results of system functionality testing carried out using black box testing. The system has been by the plan.